Isolation of Bacteriophage from Eggs and Use of Excreta as Biocontrol Agent in Controlling Eggs Related Salmonellosis (Bangladesh Journal of Microbiology, 2019)
Poultry and poultry products are the leading causes of foodborne salmonellosis worldwide. Antibiotics are used to control Salmonella spp. in poultry but its uncontrolled use results in the emergence of resistant pathogens.The use of bacteriophages as antimicrobial agents to control antibiotic resistant pathogenic bacteria could be a possible alternative. The aim of this study was to isolate, characterize and evaluate the effectiveness of bacteriophages for reducingload of Salmonella spp. on eggshells. One bacteriophage named as Sal-PE, specific to Salmonella enteritidiswas isolated from poultry excreta. For isolation, samples were subject to an enrichment protocol and then double agar layer method was performed to detect plaque. It had the capability to survive in wide range of pH between 4 to 10and found to be resistant at 60°C for 1 hour. Sal” PE showed its lytic effect on 13 of the 15 (87%) isolates including Salmonella enteritidis and Salmonella typhimurium which were recovered from 50 poultry excreta samples. After enrichment and growth on selective media, isolates were identified based on cultural characteristics, microscopic observation and biochemical tests. Amplification of three different genes (invA, sdfI, fliC) were carried out tocharacterize those isolates in molecular level. All isolates were found to be resistant to penicillin G, ampicillin, oxacillin and clindamycin but sensitive to ciprofloxacin, streptomycin, cefixime and chloramphenicol. Lytic efficiency of Sal-PE was determined by observing the reduction in optical density due to destruction of pathogens. Though more studies are needed in order to evaluate phage effectiveness, our findingsare expected to help us in initiating the development of a better preventive approach to control the occurrence of Salmonella spp. on eggshells.Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 37-44